0
$\begingroup$

This is from an Olympiad preparation course. We have to calculate the sum of the following series:

$$\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\cos({\frac{\pi n-1}{2}})}$$

I do not really know where to start, I thought about using Euler's and De Moivre's identities to work with exponentials, but I didn't get far. Wolfram evaluates the series to be equal to $1$.

Are there some general strategies in evaluating series like this or do I just try to work my way around with some complex number identity?

Thanks in advance!

$\endgroup$
3
  • 3
    $\begingroup$ Are you sure that's not supposed to be $\pi(n-1)$ instead of $\pi n - 1$ ? $\endgroup$
    – K.defaoite
    Oct 15 '20 at 14:49
  • $\begingroup$ Yes, it is definately $\frac{\pi n-1}{2}$. However, I would be interested in the way you would solve it if it were $\pi(n-1)$, as I'm looking to understand the general ideas and not just the solution to this example. I seem to understand, that you may "sum $\pi$'s if that were the case, but I don't see how this can help here. Cheers! $\endgroup$
    – Summand
    Oct 15 '20 at 14:53
  • 1
    $\begingroup$ Using the cosine addition formula you can split this into two sums $$\mathcal{S}=\sin(1/2)\sum_{n=0}^\infty \frac{\sin(n\pi/2)}{2^n n!}+\cos(1/2)\sum_{n=0}^\infty \frac{\cos(n\pi/2)}{2^n n!}$$ And then use that $\cos(n\pi/2)$ goes $1,0,-1,0....$ and $\sin(n\pi/2)$ goes $0,1,0,-1....$. I think this will lead to nicer sums. $\endgroup$
    – K.defaoite
    Oct 15 '20 at 15:01
5
$\begingroup$

\begin{align} \sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\cos\left({\frac{\pi n-1}{2}}\right)}&=\frac12\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\left(e^{i\frac{\pi n-1}2}+e^{-i\frac{\pi n-1}2}\right)}\\ &=\frac12\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}e^{i\frac{\pi n-1}2}}+\frac12\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}e^{-i\frac{\pi n-1}2}}\\ &=\frac1{2e^{i/2}}\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}e^{i\frac{\pi n}2}}+\frac{e^{i/2}}2\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}e^{-i\frac{\pi n}2}}\\ &=\frac1{2e^{i/2}}e^{e^{\pi i/2}/2}+\frac{e^{i/2}}2e^{e^{-\pi i/2}/2}\\ &=1.\\ \end{align}


Alternatively, since $\cos(\frac{\pi n-1}2)=\cos(\frac12)\cos(\frac{\pi n}2)+\sin(\frac12)\sin(\frac{\pi n}2)$,

\begin{align} \sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\cos\left({\frac{\pi n-1}{2}}\right)}&=\cos\left(\frac12\right)\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\cos\left({\frac{\pi n}{2}}\right)}+\sin\left(\frac12\right)\sum_{n=0}^{\infty}{\frac{1}{n!2^{n}}\sin\left({\frac{\pi n}{2}}\right)}\\ &=\cos\left(\frac12\right)\sum_{k=0}^{\infty}{\frac{1}{(2k)!2^{2k}}\cos(\pi k)}+\sin\left(\frac12\right)\sum_{n=0}^{\infty}{\frac{1}{(2k+1)!2^{2k+1}}\sin\left({\frac{\pi(2k+1)}{2}}\right)}\\ &=\cos\left(\frac12\right)\sum_{k=0}^{\infty}{\frac{(-1)^k}{(2k)!2^{2k}}}+\sin\left(\frac12\right)\sum_{n=0}^{\infty}{\frac{(-1)^k}{(2k+1)!2^{2k+1}}}\\ &=\cos\left(\frac12\right)\cos\left(\frac12\right)+\sin\left(\frac12\right)\sin\left(\frac12\right)\\ &=1.\\ \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.